Sharp Changes in Muscle Tone in Humans Under Simulated Microgravity - Amirova, Liubov E.; Plehuna, Anastasija; Rukavishnikov, Ilya V.; Saveko, Alina A.; Peipsi, Aleko; Tomilovskaya, Elena S. (Frontiers in Physiology, 2021)
Space flight-induced muscle tone decrease requires a standardized assessment of changes as a necessary step for controlling the neuromuscular system state. This study is a step towards the development of a unified protocol and was aimed at determining the immediate effect of support presence or withdrawal on muscle tone, the effects of two-hour supportlessness in Dry Immersion (DI), and the changes in muscle tone depending on the measurement site. The MyotonPRO device was used to perform all measurements of the muscle tone changes. The list of muscles assessed includes: trunk - mm. Posterior deltoid, Trapezium, Erector spinae; leg - mm. Biceps femoris, Rectus femoris, Tibialis anterior, Soleus, Gastrocnemius; foot – m. Flexor digitorum brevis, and Achilles tendon, Plantar aponeurosis. The study involved 12 healthy volunteers (6 men, 6 women) without musculoskeletal disorders and aged 32.8±1.6 years. A significant decrease in muscle tone was observed at the start and continued to intensify for two hours into DI in the following: Tibialis anterior (-10.9%), Soleus (-9.6%), Erector spinae (-14.4%), and the Achilles tendon (-15.3%). In contrast, Gastrocnemius muscle demonstrated an increase in muscle tone (+7.5%) at 2 hours into DI against the immediate in-bath baseline. Muscle tone values have been observed to be site-dependent and altering in different projections of Erector spinae and Soleus. High sensitivity of the myotonometry technique was observed in the previous experience and confirmed by this study. A standardized protocol for measuring muscle tone for general use in gravitational physiology to compare data from different studies requires development.